New species and new records of Renda Blackwelder, 1952 (Coleoptera: Staphylinidae: Xantholinini) from Brazil, with an updated key to the species of the genus - Klemann-Junior, Louri; Barroso, Paulo Ricardo Ramires; Márquez, Juan (Zootaxa, 2025)
We describe three new species of the genus Renda Blackwelder, 1952 (Coleoptera: Staphylinidae: Xantholinini), R. aneba Klemann-Junior, Barroso & Márquez sp. nov., R. boiuna Klemann-Junior, Barroso & Márquez sp. nov., and R. carauariense Klemann-Junior, Barroso & Márquez sp. nov., from Amazonas state, in the north of Brazil. We illustrate major diagnostic features and include the new species in the key to Renda species published by Márquez (2010). In addition, we present new distribution records for R. brachyptera (Sharp, 1885), R. brasiliana (Bernhauer, 1927), R. cariniventris Márquez, 2010, R. clavicornis (Sharp, 1876), R. fimetaria (Sharp, 1876), R. formicaria (Laporte, 1835), R. minor (Sharp, 1876), and R. ophthalmica Márquez, 2010 from Brazil. Renda brachyptera and R. ophthalmica are recorded for the country for the first time.